2011
DOI: 10.1016/j.rgg.2010.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Complete isomorphic join diopside–kosmochlor CaMgSi2O6–NaCrSi2O6 in metamorphic rocks of the Sludyanka complex (southern Baikal region)

Abstract: Chromium and vanadium-bearing metamorphic derivatives of siliceous-carbonate sediments in the Sludyanka granulite-facies complex, southern Baikal, contain high-Cr clinopyroxenes that belong to the diopside–kosmochlor–natalyite join (CaMgSi2O6–NaCrSi2O6–NaVSi2O6). The ternary join includes isomorphic binary joins of which the diopside–kosmochlor join with 94% kosmochlor (Kos) end-member has been studied in detail and found to be virtually complete. As indicated by signature of diopside–eskolaite reactions in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…However, no eskolaite was found in the samples investigated here, which could be the result of its instability in the observed paragenesis owing to Na input via metasomatism (extensive fenitization is known from the Samalpatti complex; e.g., [21]) and resulting formation of Di-Kos solid solution as proposed by Vasil'ev et al [32], or formation of Cr-rich pyroxene by another process. Eskolaite could also be the source for formation of magnesiochromite as proposed by Reznitsky et al [2] via the reaction (2):…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
See 3 more Smart Citations
“…However, no eskolaite was found in the samples investigated here, which could be the result of its instability in the observed paragenesis owing to Na input via metasomatism (extensive fenitization is known from the Samalpatti complex; e.g., [21]) and resulting formation of Di-Kos solid solution as proposed by Vasil'ev et al [32], or formation of Cr-rich pyroxene by another process. Eskolaite could also be the source for formation of magnesiochromite as proposed by Reznitsky et al [2] via the reaction (2):…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…The other two end members are jadeite (NaAlSi 2 O 6 ) + aegirine (NaFeSi 2 O 6 ) [1] and diopside (MgCaSi 2 O 6 ), and kosmochlor forms a solid solution with each of these. Reznitsky et al [2] found…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Trace and minor elements are also used to investigate diffusivity in minerals and associated timescales (John et al, 2012;Ague and Axler, 2016), constrain pressure-temperature-time paths, and study metasomatism (e.g. Hickmott and Shimizu, 1990;Rubatto and Hermann, 2003;Angiboust et al, 2014;S. Figowy et al: Partitioning of chromium between garnet and clinopyroxene Kohn, 2014).…”
Section: Introductionmentioning
confidence: 99%